Trends in Human Resource Management in the New Technological Era - Athira S (PT FORMOSA CENDEKIA GLOBAL, 2022)
Human Resource Management is considered as one of the very important function of in every organisation. HRM is called as the heart and soul of a business, without which the organisation would not be able to effectively recruit and retain employee and they wouldn’t be able to maintain the organisation healthy. Mathis and Jackson have defined “HRM is the effective use of human resources and organisation through the management of people related activities”. The importance of human resource management is immense as many functions are there to human resource management that helps an organisation stay successful. Their duties and responsibilities in the organisation is very wide. It ranges from recruitment and training to managing disputes, maintaining a healthy work life balance, and all payroll responsibilities.Inspite of all these responsibilities, the role of HR department is heightened at the arrival of the pandemic. The situation was a new challenge to the HR professionals for running the organizational functions uninterrupted. At the same time it was an opportunity to the HR practitioners to rethink about their current practices and policies.